2017
DOI: 10.18203/2394-6040.ijcmph20172847
|View full text |Cite
|
Sign up to set email alerts
|

Health status of primary school children: study from a rural health block of Lucknow

Abstract: Background: School health is an important branch of community health. School health services is an economical and powerful means of raising community health. In school child is vulnerable to stress, tension and endangerment of group life because all children are not the same and comes from different socioeconomic and cultural background and with different immunity status. Child is quite vulnerable at this growing age and hence become easy victims of many non-communicable diseases such as dental caries, anaemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 3 publications
3
12
2
Order By: Relevance
“…Also, 10.3% had signs of vitamin deficiencies. Asghar et al in their study found 37.05% had dental caries and 10% had ear discharge and vitamin A deficiency in 4.70% (Asghar, 2017).…”
Section: Discussionmentioning
confidence: 87%
“…Also, 10.3% had signs of vitamin deficiencies. Asghar et al in their study found 37.05% had dental caries and 10% had ear discharge and vitamin A deficiency in 4.70% (Asghar, 2017).…”
Section: Discussionmentioning
confidence: 87%
“…Similar results were found by Asghar et al in Lucknow where total number of school children enrolled in the study was 170 and among these 82 (48%) were boys and 88 (52%) were girls. 3 While in a study at Meerut, girls were 46.8% and boys were 53.3%. 4 Most common morbidity found was caries (61.1%) followed by ear wax (38.1%).…”
Section: Discussionmentioning
confidence: 96%
“…Asghar et al in their study found 37.05% had dental caries and 10% had ear discharge and vitamin A deficiency in 4.70%. 3 Study in rural area of Lucknow showed vitamin A deficiency in 46.3%. 5 Another study in Urban area of Guntur showed 14.85% had dental caries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample size has been calculated considering the prevalence obtained for underweight in the study Abid et al, which is 40%. 10…”
Section: Methodsmentioning
confidence: 99%